Noise-Induced Hearing Loss Prevention: Role of Occupational Health Nurse - Ritngam, Arisara (Journal of Public Health Nursing, 2018)
Noise-induced hearing loss is a disease concerning sensorineural hearing loss caused by prolonged exposure to loud noise. Currently, prevention is the best deterrence. Hearing loss prevention programs can encourage employers to minimize the risk of noise-induced hearing loss to employees. The 8 main comprehensive components of a hearing loss prevention program to solve the problem including 1) auditing 2) noise exposure monitoring 3) engineering and administrative controls 4) audiometric evaluation and referral 5) personal hearing protection devices 6) education and motivation 7) record keeping and 8) program evaluation. Hearing loss programs require cooperation from all parties in the workplace. The occupational health nurse (OHN) plays an important role in preventing noise-induced hearing loss by generating knowledge, understanding and awareness of the dangers of noise and behavior of protection from noise. However, at present OHNs are unable to fully fulfill their roles because they lack knowledge and acceptance from the employer. Therefore, OHNs should learn more about preventing noise-induced hearing loss and practice skills related to gaining greater expertise to be better able to care for workers at risk of noise-induced hearing loss completely.